Metabolomic insights into amino acid signatures and pathways associated with osteoporosis in Iranian elderly population - Hojat Dehghanbanadaki; Azin Soltani; Azin Soltani; Ziba Majidi; Mostafa Rezaei-Tavirani; Gita Shafiee; Afshin Ostovar; Fatemeh Bandarian; Niloufar Najjar; Bagher Larijani; Iraj Nabipour; Patricia Khashayar; et al. (Frontiers in Medicine)
BackgroundOsteoporosis poses a serious health risk to the elderly, particularly in developing countries like Iran. We aimed to determine the 20-amino acids-signatures and pathways associated with osteoporosis in the Iranian elderly population.MethodsWe analyzed the data from the Bushehr Elderly Health Program (BEHP). In the BEHP cohort, participants aged 50 and older in Bushehr, Iran were selected using a multistage stratified random sampling approach. We used logistic regression, pathway enrichment, and pathway impact analysis to determine the metabolites and pathways altered in osteoporosis. AUC-ROC curve analysis assessed the clinical significance of metabolites in differentiating between osteoporosis and control groups.ResultsThis study included 1916 participants (1,097 women and 819 men). In women, glycine, citrulline, serine, and aspartic acid were associated with 27, 25, 23, and 21% higher risk of osteoporosis. In men, tyrosine, leucine, valine, and lysine were related with a 24, 22, 22, and 22% reduction in the risk of osteoporosis, respectively. The most impactful altered metabolite pathway among the osteoporotic individuals was “phenylalanine, tyrosine and tryptophan biosynthesis” in both genders. In women, citrulline had an AUC of 0.63 for distinguishing between individuals with osteoporosis and healthy controls. In men, valine, leucine, and tyrosine showed AUC values of 0.62, 0.61, and 0.61, respectively.ConclusionOsteoporosis is associated with altered serum amino acids levels in both men and women. The condition is associated with several altered metabolic pathways, with “phenylalanine, tyrosine, and tryptophan biosynthesis” being the most important one. These metabolite signatures and pathways could be targeted for the prevention and management of osteoporosis in older adults.